Beyond the media boundaries: Analysing how dominant genre devices shape our narrative knowledge. (December 2017) - Tseng, Chiao-I
Abstract: This article investigates the hypothesis that genres are social-cultural categories that surpass the boundaries of media and shape our narrative expectations. In this pursuit, it proposes analytical methods for analysing significant genre dimensions such as characters' motivations and event developments. Several studies have shown how many aspects of television and cinema exhibit a reliance on genre and how genres operate within industry, audience and cultural practices. By applying the analytical methods of event and motivation in film, comics and novels, this paper unravels just how narrative patterns across these media have some shared generic identity, fitting into well-entrenched generic categories or incorporating similar forms of genre hybridity.